1988
DOI: 10.1037/0022-3514.55.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Consensus in personality judgments at zero acquaintance.

Abstract: This research focused on the target effect on a perceiver's judgments of personality when the perceiver and the target are unacquainted. The perceiver was given no opportunity to interact with the target, a condition we refer to as zero acquaintance. We reasoned that in order to make personality judgments, perceivers would use the information available to them (physical appearance). Consensus in personality judgments would result, then, from shared stereotypes about particular physical appearance characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
366
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(414 citation statements)
references
References 29 publications
43
366
0
5
Order By: Relevance
“…The evidence indicates that attitude formation is better described as a set of automatic processes than as a process of deliberation and reflection about the traits of a person. People form first impressions at first sight (Albright, Kenny, & Malloy, 1988), and the impressions that they form from observing a "thin slice" of behavior (as little as 5 seconds) are almost identical to the impressions they form from much longer and more leisurely observation and deliberation (Ambady & Rosenthal, 1992). These first impressions alter subsequent evaluations, creating a halo effect (Thorndike, 1920), in which positive evaluations of non-moral traits such as attractiveness lead to beliefs that a person possesses corresponding moral traits such as kindness and good character (Dion, Berscheid, & Walster, 1972).…”
Section: ) the Dual Process Problem: There Is A Ubiquitous And Undermentioning
confidence: 99%
“…The evidence indicates that attitude formation is better described as a set of automatic processes than as a process of deliberation and reflection about the traits of a person. People form first impressions at first sight (Albright, Kenny, & Malloy, 1988), and the impressions that they form from observing a "thin slice" of behavior (as little as 5 seconds) are almost identical to the impressions they form from much longer and more leisurely observation and deliberation (Ambady & Rosenthal, 1992). These first impressions alter subsequent evaluations, creating a halo effect (Thorndike, 1920), in which positive evaluations of non-moral traits such as attractiveness lead to beliefs that a person possesses corresponding moral traits such as kindness and good character (Dion, Berscheid, & Walster, 1972).…”
Section: ) the Dual Process Problem: There Is A Ubiquitous And Undermentioning
confidence: 99%
“…They defined high-intensity negativity as contempt, defensiveness, and belligerence whereas anger was classified as low-intensity negativity. (Albright, Kenny, & Malloy, 1988;Ambady & Rosenthal, 1992Paunonen, 1991;Rosenthal, Blanck, & Vannicelli, 1984). …”
Section: Using Human Beings' Naturally Honed Abilities To Recognize Ementioning
confidence: 99%
“…This is known as consensus at zero acquaintance (Albright, Kenny, & Malloy, 1988). Most studies using a zero-acquaintance paradigm give observers access to static information that may have an impact on perceived personality; for instance, a neat attire and being well groomed have an impact on perceived conscientiousness and extraversion (Albright, et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This is known as consensus at zero acquaintance (Albright, Kenny, & Malloy, 1988). Most studies using a zero-acquaintance paradigm give observers access to static information that may have an impact on perceived personality; for instance, a neat attire and being well groomed have an impact on perceived conscientiousness and extraversion (Albright, et al, 1988). However, some studies have reported consensus at zero acquaintance based on point-light stimuli (Brownlow, Dixon, Egbert, & Radcliffe, 1997;Heberlein, Adolphs, Tranel, & Damasio, 2004;Montepare & Zebrowitz-McArthur, 1988).…”
Section: Introductionmentioning
confidence: 99%